Fighting a war without weapons? Lessons from the COVID‐19 outbreak - Vasileiou, Evangelos (World Med Health Policy, 2021)
The recent pandemic of COVID‐19 revealed that a highly transmissible virus threatens all humanity because extensive mobility, migration, and millions of passengers who travel worldwide shape our globalized environment and make containment of a virus more difficult. In a war between humans and viruses, we should have the necessary weapons, such as masks, gloves, ventilators, and so forth. However, during the COVID‐19 outbreak, there was a shortage of this basic medical and personal protective equipment (MAPPE), even for the health workers. This note focuses on this issue and suggests that a global organization, which stores and renews basic MAPPE would be beneficial in the fight against the next pandemic and that such an organization can be established without significantly increasing the public expenses of the countries.